Strategies for Preparing Sustainability Reports to Enhance Stakeholder's Trust in Medium-Sized Companies - Barnabas Tridig Silaban; Raden Roro Atiqah Sekararum Dewanti Meliala; Jesslyn Febe (Jurnal Ragam Pengabdian, 2025)
Sustainability reporting is one of the important focuses in modern accounting practices because it plays a role in building stakeholder trust in corporate integrity and social responsibility. In the context of medium-sized companies, the process of preparing sustainability reports often faces challenges in the form of limited resources, technical capabilities, and an understanding of international reporting standards. This research was conducted to explore the strategies used by medium-sized companies in preparing sustainability reports to increase stakeholder trust. A descriptive qualitative approach with multiple case study designs is used to understand the company's practices and experiences in the reporting process. Data was collected through semi- structured interviews with 12 informants consisting of managers and sustainability officials from six medium-sized companies in the manufacturing and service sectors, as well as through the analysis of published sustainability report documents. The data was analyzed using thematic analysis techniques to find patterns of strategies and factors that affect the formation of trust. The results show that active stakeholder engagement, narrative transparency in reporting, third-party assurance, and the suitability of environmental and social indicators with the business context are the main strategies that build trust. This study concludes that the implementation of adaptive and participatory reporting strategies contributes to increasing the credibility and legitimacy of medium- sized companies. These findings provide the basis for the development of contextual sustainability reporting guidelines oriented towards strengthening public trust.